2017
DOI: 10.1093/icvts/ivx099
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of aortopulmonary window: 24 years of experience and lessons learned

Abstract: Aortopulmonary window is a rare but well identified and surgically correctable anomaly. Operative repair should be offered as soon as the diagnosis is established, regardless of the patient's age. Irreversible pulmonary hypertension with a right to left shunt despite oxygen administration is the only contraindication for surgery. Various surgical techniques can be applied depending on the size of the communication. Associated arch anomalies may require technically challenging approaches and surgical strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Although anomalous origin of the coronary artery (right or left) from the pulmonary trunk has been reported in APW, coronary artery anomalies were unlikely to be diagnosed prenatally and should be looked for postnatally prior to surgery . Nowadays, the “sandwich” repair described by Johansson and colleagues entailing a transwindow approach and defect closure is the most widely used technique . In general, surgery involves separation of the great arteries with either suture division or patch closure of the aorta and PA.…”
Section: Discussionmentioning
confidence: 99%
“…Although anomalous origin of the coronary artery (right or left) from the pulmonary trunk has been reported in APW, coronary artery anomalies were unlikely to be diagnosed prenatally and should be looked for postnatally prior to surgery . Nowadays, the “sandwich” repair described by Johansson and colleagues entailing a transwindow approach and defect closure is the most widely used technique . In general, surgery involves separation of the great arteries with either suture division or patch closure of the aorta and PA.…”
Section: Discussionmentioning
confidence: 99%
“…APW infants can be an indication for immediate surgery to prevent congestive heart failure and irreversible pulmonary vascular changes. Without surgery, 40% to 50% of infants will die within one year after birth 2,14,15 . The prognosis is usually associated with other cardiac malformations.…”
Section: Discussionmentioning
confidence: 99%
“…The major decision factors in the treatment of children presenting with defects beyond infancy are the assessment of operability, the postoperative management of pulmonary hypertension, and long-term outcomes [4] . Previous reports demonstrated favorable early and long-term outcomes after surgical correction, regardless of age or pulmonary vascular resistance [2,3] . Based on these reports, we decided to proceed with the surgical repair of the defect in the subject.…”
Section: Discussionmentioning
confidence: 99%
“…According to Stansel et al [1] , only less than 100 cases have been reported to date. The defect is located between the ascending aorta and the common pulmonary artery and is associated with a rapid progression of pulmonary arterial hypertension, unless it is corrected surgically [2] . Its pathophysiology and clinical manifestations resemble those of patent ductus arteriosus.…”
Section: Introductionmentioning
confidence: 99%